Activarse desde la periferia. Estrategias y tácticas de desplazamiento en bicicleta y a pie en El Rincón de Suba (Bogotá) - Ducasse, Arthur (2024)
This paper intends to describe tactics and strategies that dwellers of El Rincon in Bogota adopt during their daily journeys walking or cycling. El Rincon is a neighborhood, and a zoning unit for planning (UPZ, unidad de planeamiento zonal) located in the north-western end of the city, in Suba locality. Its high population density and its uneasy-to-access topography turned out to be two main aspects of this study. The research is based on a long-term ethnographic field work (from February 2021 to July 2022). Observations of cycling and walking mobilities, semi-structured interviews and ride-along interviews were implemented to describe the strategies the inhabitants elaborate to leave El Rincón, and the tactics they use to move about in this congested environment. Walking and cycling appear to help mitigate congestion’s impacts and allow better control on daily journey’s length and conditions.